A monolithically integrated, intrinsically safe, 10% efficient, solar-driven water-splitting system based on active, stable earth-abundant electrocatalysts in conjunction with tandem III–V light absorbers protected by amorphous TiO2 films. Issue 11 (27th August 2015) - Verlage, Erik; Hu, Shu; Liu, Rui; Jones, Ryan J. R.; Sun, Ke; Xiang, Chengxiang; Lewis, Nathan S.; Atwater, Harry A.
Abstract : A monolithically integrated device, protected by a TiO2 stabilization layer, splits water using sunlight. Abstract : A monolithically integrated device consisting of a tandem-junction GaAs/InGaP photoanode coated by an amorphous TiO2 stabilization layer, in conjunction with Ni-based, earth-abundant active electrocatalysts for the hydrogen-evolution and oxygen-evolution reactions, was used to effect unassisted, solar-driven water splitting in 1.0 M KOH(aq). When connected to a Ni–Mo-coated counterelectrode in a two-electrode cell configuration, the TiO2 -protected III–V tandem device exhibited a solar-to-hydrogen conversion efficiency, η STH, of 10.5% under 1 sun illumination, with stable performance for >40 h of continuous operation at an efficiency of η STH > 10%. The protected tandem device also formed the basis for a monolithically integrated, intrinsically safe solar-hydrogen prototype system (1 cm 2 ) driven by a NiMo/GaAs/InGaP/TiO2 /Ni structure. The intrinsically safe system exhibited a hydrogen production rate of 0.81 μL s −1 and a solar-to-hydrogen conversion efficiency of 8.6% under 1 sun illumination in 1.0 M KOH(aq), with minimal product gas crossover while allowing for beneficial collection of separate streams of H2 (g) and O2 (g).